A rare presentation of post hysterectomy retroperitoneal haematoma - Rana, A.; Gurung, G.; Bista, K.D.; Singh, K.P.; Ghimire, R.K. (Journal of Institute of Medicine Nepal, 2007)
Post-hysterectomy adynamic ileus, which improved after spontaneous resolution of peri renal retroperitoneal haematoma, is reported. Journal of Institute of Medicine Vol.27(3) 2005